Design Features of a Removable Module Intended for Securing Containers When Transported in an Open Wagon - Alyona Lovska; Juraj Gerlici; Ján Dižo; Mykhailo Pavliuchenkov; Pavlo Rukavishnikov (Applied Sciences)
The design of a removable module is proposed in order to enable the use of open wagons for container transportation. This module secures a container placed on an open wagon considering conditions for its strength under conditions of the operational load. The use of rectangular pipes was proposed as profiles for the removable module. The possibility of optimizing the cross-section parameters of the beams of the removable module frame was investigated. The optimization was carried out according to the criterion of a reduction in the material consumption of the removable module frame. It was established based on the preformed calculations that this optimization contributes to reducing the unit mass of the frame beam by 1.5% compared to using a typical rectangular profile. A spatial model of the removable module was built, and its strength was calculated considering the results of the optimization process. The results of the calculations show that the strength of the removable module is ensured under the considered load schemes. Moreover, within the framework of the research, an experimental study of the hatch cover strength of an open wagon when loaded by the removable module was carried out. At the same time, experimental tests were carried out in laboratory conditions using the method of the electrical strain gage. It was established that the strength of the hatch cover is maintained. The conducted research will contribute to the creation and development of the use of open wagons for container transportation and, accordingly, to increasing the efficiency of containerized cargo transportation, including in international traffic.